Pomeranchuk instabilities in holographic metals - Giordano, Gastón Luciano (2021)
We develop a method to detect instabilities leading to nematic phases in strongly coupled metallic systems. We do so by adapting the well-known Pomeranchuk technique to a weakly coupled system of fermions in a curved asymptotically AdS bulk. The resulting unstable modes are interpreted as corresponding to instabilities on the dual strongly coupled holographic metal. We apply our technique to a relativistic 3 + 1- dimensional bulk with generic quartic fermionic couplings, and explore the phase diagram at zero temperature for finite values of the fermion mass and chemical potential, varying the couplings. We find a wide region of parameters where the system is stable, which is simply connected and localized around the origin of coupling space.